(untitled) (Bangladesh Journal of Urology, 2020)
Objective :To find out the outcome of Percutaneous Nephrolithotomy Methods:This prospective study was done in the Department of Urology, ShaheedSuhrawardy Medical College Hospital, Dhaka during the period of July 2016 to June2017 .Thirty five patients with renal calculi were included in this study. All patients wereevaluated by history, physical examination and investigations. Patients were counseledfor PCNL it was done under sub-arachnoid block in all the cases. Intra operativecomplications in terms of bleeding requiring blood transfusion, pleural injury, renal pelvisinjury, were recorded. Stone clearance were also recorded. Postoperative complicationswere also recorded in predesigned data sheet. Data analyses were done by SPSS –WIN 10.0 version. Result: Mean age of the patients was 41.5±10.23 years and mean size of the stonewas 2.58±.96cm. Mean operative time was121.7 minute. Stone clearance rate was 80%and residual stone was in 20% cases. Different complications were recorded in 42.85%cases. Hospital stay was 4.65±2.24 days. Conclusion: Percutaneous Nephro-lithotomy is a good option in the management ofrenal calculi .It has good stone clearance rate, lower morbidity , shorter hospital stayand early return to work. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.80-84